2012
DOI: 10.4321/s0213-61632012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, occupational stressors, and social support in psychiatric and medical trainees

Abstract: -Background and Objectives: Although previous research reports that psychiatrists experience greater work-related distress than other specialties, very little is known about how psychiatric trainees compare to their medical colleagues. The aim of this study was to compare psychiatric and general medical trainees in burnout, work stressors, and social support and investigate potential buffering effects of social support.Methods: This cross-sectional study included 112 psychiatric and 72 general medical trainees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Overall, 1659 psychiatrists (or doctors working in psychiatry) were included in the meta-analysis. Of the studies included, three were from the United Kingdom (UK), 9-11 two were from New Zealand, 12,13 two were from Italy, 14,15 one was from Japan, 16 one was from Germany 10 and one was from Turkey. 17 Additionally, Gül et al 17 reported two samples (adult psychiatrists and child and adolescent psychiatrists).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 1659 psychiatrists (or doctors working in psychiatry) were included in the meta-analysis. Of the studies included, three were from the United Kingdom (UK), 9-11 two were from New Zealand, 12,13 two were from Italy, 14,15 one was from Japan, 16 one was from Germany 10 and one was from Turkey. 17 Additionally, Gül et al 17 reported two samples (adult psychiatrists and child and adolescent psychiatrists).…”
Section: Resultsmentioning
confidence: 99%
“…Research has established a link between social support, burnout, work satisfaction, and productivity, with social connectivity resulting in greater psychological well-being, higher productivity, and better performance. 6 If social isolation in health professional students can be prevented by monitoring for risk, implementing interventions to improve meaningful socialization, and teaching students strategies to optimize wellness, perhaps rates of student burnout can be lowered and wellness optimized.…”
Section: Activities Encouraging Socializationmentioning
confidence: 99%
“…2,3 One factor found to promote personal well-being and reduce burnout is social support, which reduced the need for medication, prevented pathological states including depression and alcoholism, and helped the body recover faster. [4][5][6][7] In a study of medical residents, loneliness was associated with burnout in a dose-dependent (ie, as burnout increases, loneliness increases and vice-versa) fashion. 8 Despite the knowledge that loneliness and burnout coexist, the specific factors that contribute to health professionals' feelings of isolation or "loneliness" are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, coping patterns oriented toward problem solving have been found effective in stressful situations and correlate with improved effective cognitive functioning and positive feelings among therapists, which in turn improve their capacity to cope with changes (Ben-Zur & Yagil, 2005). Among the factors mitigating the negative consequences of work-related pressure for therapists, social support has been identified as a protective factor against burnout (Sochos & Bowers, 2012). Working team cohesion, mutual support, and psychological debriefing and supervision sessions have each been selected as highly effective coping strategies for therapists repeatedly exposed to their clients' traumas (Collins & Long, 2003;Marriage & Marriage, 2005).…”
Section: Copingmentioning
confidence: 99%